Rise and Fall of the Carbon Civilisation Resolving Global Environmental and Resource Problems - Moriarty, Patrick; Honnery, Damon (Green Energy and Technology,, 2011)
A vast amount has been written on climate change and what should be our response. Rise and Fall of the Carbon Civilisation suggests that most of this literature takes a far too optimistic position regarding the potential for conventional mitigation solutions to achieve the deep cuts in greenhouse gases necessary in the limited time frame we have available. In addition, global environmental problems, as exemplified by climate change, and global resource problems - such as fossil fuel depletion or fresh water scarcity - have largely been seen as separate issues. Further, proposals for solution of these problems often focus at the national level, when the problems are global. The authors argue that the various challenges the planet faces are both serious and interconnected. Rise and Fall of the Carbon Civilisation takes a global perspective in its treatment of various solutions: • renewable energy; • nuclear energy; • energy efficiency; • carbon sequestration; and • geo-engineering. It also addresses the possibility that realistic solutions cannot be achieved until the fundamentally ethical question of global equity - both across nations today and also inter-generational - is fully addressed. Such an approach will also involve reorienting the global economy away from an emphasis on growth and toward the direct satisfaction of basic human needs for all the Earth's people. Rise and Fall of the Carbon Civilisation is aimed at the many members of the public with an awareness of climate change, but who wish to find out more about how we need to respond to the challenge. It will also be of interest to technical professionals, as well as postgraduate students and researchers, from the environmental and engineering science sectors.